Standardization of Paku Lindung extract (Pneumatopteris callosa (Blume)) - Fauzi, Muh Fajar; Widyaningsih, Wahyu (Media Farmasi: Jurnal Ilmu Farmasi, 2024)
The standardization of the paku lindung extract was carried out to obtain new data regarding the standardization of the hedgehog extract which had not previously been established. In addition, this determination is carried out to obtain quality preparations in the form of a guarantee process, that the extract obtained has certain parameter values that are constant after the data has been determined. Extract standardization test includes specific parameters including organoleptic, soluble compounds in certain solvents. Non-specific parameter tests include drying shrinkage, moisture content, ash content, heavy metal contamination, microbial contamination. Chemical content test includes chromatogram pattern, determination of total flavonoid content. The yield of the resulting extract was 13.88±3.19% g. The test results of non-specific parameters include drying shrinkage 0.47±0.01%, moisture content 8.28±0.16%, total ash content 18.97±3.53%, acid insoluble ash content 1.69± 0.02%, total plate number 7.8x104±12.91 colonies/gram, yeast mold number 1x102±0.24 colonies/gram, heavy metal contamination of Cd, Cr and Pb negative and Fe of 73.88 ppm. The results of the specific parameter test include 85.55±4.29% water soluble compounds, 31.27±5.06% ethanol soluble compounds. The results of the chemical content test included the total flavonoid content of 16.6±17.60 mgEQ/g, the Rf value of the extract was the same as the Rf of quercetin with 5 variations of the mobile phase. The test results were carried out to meet the predetermined determination and provide new data on the standardization of the paku lindung extract.